Analisis Gangguan Cadel Pada Anak Usia 5 Tahun:Kajian Psikolinguistik - Ayis Sukmawati; Hendra Setiawan (Peneliti.net, 2023)
This research aims to identify the causes of stuttering in children. The research object is a five-year-old child who still experiences stuttering when producing speech. Data collection is done using the observation technique by conducting direct interviews with the sufferer. Then the data is recorded and classified for analysis. The results show that the child is diagnosed with a speech disorder in the form of stuttering due to several factors, namely psychological factors, neurological disorders, and developmental disorders that are hindered by the family environment.